The urbanisation on the slopes of Sarajevo and the rise of geomorphological hazards during the post-war period - Martín-Díaz, Jordi (2019)
Within the interdisciplinaryfield of urban geomorphology, scholars have recently paid attention to the in-creasing vulnerability of landscapes, due principally to the construction of housing and infrastructure. Withregard to the case of Sarajevo and more specifically the capital of Bosnia and Herzegovina, historically, itsparticular geographic setting has maintained a central role in the spatial distribution of its population, withresidential areas exposed to potential geomorphological hazards. Urbanisation on the slopes of Sarajevo wasresumed after the Bosnian War (1992–1995) in areas with steep slope gradients. This was a consequence of theimpossibility or unwillingness of those internally displaced, sheltered in Sarajevo during the conflict, to return topre-war homes. Thus, this paper explores the political, social and economic factors that have influenced both thehistorical process of urbanisation on the slopes, surrounding the central areas of the city, and its subsequentreproduction during the post-war period. The aim of this paper is to evaluate the exposition of these urbanisedslopes to potential geomorphological hazards. Moreover, the extent of urbanisation on the slopes will bequantified infive study areas for periods between 1987–2003 and 2003–2015. It precedes the evaluation of thegeomorphological vulnerabilities of constructions developed in these sites. Finally, corrective measures areproposed in the current process of elaboration of the new Urban and Strategic Plans.